Corazon de Madera revitalizing the community of Paete through its traditional arts - Castro, Noel I.; Balane, Ronald S. (Quezon City College of Architecure, University of the Philippines Diliman, 2018)
The Comprehensive Design Project is based on the town of Paete, approximately a hundred kilometers Southeast of Metro Manila. Months of observation and immersion led the designer to issues which include an underdeveloped sociocultural framework for the Community, a lack of a consistent tourism base, and the absence of its own distinguishable architecture founded upon history and art. With this, the Corazon de Madera was created. It is an institution which aims to serve as a center for promoting tradition within and beyond the community of Paete. Founded upon the town's reputation to be the Woodcarving Capital of the Philippines. CDM offers a traditional arts program which is open to culture enthusiasts who desire to immerse into the warm Paeteno Community. Aside from possessing exhibitory spaces, the CDM offers workshops and places for retail, with which it shall establish a new brand of tourism that adapts to the demands of today's society by utilizing its culture. Corazon de Madera is design according to the dictates of its art, attempting to establish an architectural identity that preserves its art, embodies its community, and carries the whole towards the future.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Arts facilities; Arts facilities -- Paete -- Laguna -- Philippines